PROPOSTA DE ORDENAMENTO TERRITORIAL DA BACIA HIDROGRÁFICA DO RIO BARREIRO BASEADA EM ÍNDICES DE REPRESENTAÇÃO DO RELEVO: ALTERNATIVA PARA O DESENVOLVIMENTO COMUNITÁRIO - Nadal, Karla (2023)
Changes in land use and land cover have compromised the maintenance and conservation of ecosystems, resulting in damage to the environment, the economy and the well-being of society. In view of this issue, the integrated analysis of the physical environmental characteristics allows the inference of the limitations and aptitudes of soil use. Anchored in this perspective, this research aimed to analyze the application of Relief Representation Indices (RRI) as a tool to guide the Territorial Planning of the Barreiro River Basin (TPBRB), located in the Municipality of Fernandes Pinheiro, Paraná State, Brazil. To this end, attributes resulting from the Numerical Terrain Model (NTM) were generated, namely: Altitude Above Channel Network (AACN) - altitude in relation to the drainage channel, Topographic Wetness Index (TWI) - moisture index, Multiresolution Index of Valley Bottom Flatness (MRVBF) - erosion potential, Ls Factor (LS Factor) - product of the relationship between slope and slope length and Slope - slope. The processing of the RRI resulted in obtaining the Limiting Classes classified as Apt, Moderate, Restricted and Inapt, thus denoting the levels of physical environmental fragility in the TPBRB. Then, in the search for compatibility between land use and Limiting Classes, a Cross Tabulation was performed, generating the Land Use Conditions map, which presented three Classes: Adequate, Underutilized and Overutilized. The Barreiro River Basin registered an Overutilized Use Condition in about 34% (2279,84 hectares) of its area. It was also found that in approximately 23% (1511,45 hectares) of the studied area the land use is below its suitability (Underutilized). The sites classified as Adequate Use Condition represented 43% (2865,15 hectares) of the Watershed. With this information, it can be stated that 66% of the study area has a use compatible with the environmental conservation of the basin. The study also included semi-structured interviews with rural producers and agricultural technician of the Rural Development Institute (IDR), Municipal Unit of Fernandes Pinheiro, Paraná State, Brazil, who expressed their perception of land use. It was verified the consent of the producers in relation to the conservation of natural resources; however, when pointing to the need for changes, there is some resistance to break with traditional practices. The results of the research demonstrate its innovative nature and ratified the feasibility of applying the RRI as a support to the determination of the physical environmental fragility and subsidy to the elaboration of proposals for territorial planning of hydrographic basins, due to its reliability, celerity and possibility of association with soil conditions. In addition, the study may serve as technical-scientific support for the implementation of public policies based on the conservation of natural resources, based on guidelines that align with the Sustainable Development Goals (SDGs), enhancing agricultural productivity, income generation and improving the living conditions of the population.